Development of a scale to measure individual creativity constraints. (28th October 2019) - Sharma, Tripti; Mishra, P.N.
Individual creative thinking is subject to some major constraints. These constraints are real obstacles to problem solving skills of employees who drive the business in terms of creative thinking. If these constraints are removed then creativity can flourish, fill a new niche, increase productivity, improve services, develop new uses for existing products and provide solution to existing challenges of varied businesses. The interest in individual creative construct has gained increasing momentum in recent years. Till now, the measurement tools have focused on individual and organisational creativity. However, no measure of individual creativity constraints (ICC) has been advanced despite of persistent requirement in the research. The main aim of this research study is to develop a scale on ICC. This article presents the methodological rigour in development of a scale, which is valid and reliable. It is developed for the use in the human resources and behavioural science to measure ICC.